Talent Detection in Taekwondo Practitioners - Willy Pieter (Universidad de León, 2012)
An overview is presented of characteristics of young taekwondo athletes that are believed to contribute to performance. Findings from the scientific literature were summarized to highlight the current knowledge regarding physical and psychological components that are deemed important to be successful in competition. To increase the chances of taekwondo youngsters in becoming adult champions, optimal infrastructure, well-educated coaches, qualified sport scientists, and informed governing bodies are needed.